2005
DOI: 10.1021/ac0510888
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Platform for Liquid Chromatography−Tandem Mass Spectrometry Analyses of Complex Peptide Mixtures

Abstract: A microfluidic chip that integrates all the fluidic components of a gradient liquid chromatography (LC) system is described. These chips were batch-fabricated on a silicon wafer using photolithographic processes and with Parylene as the main structural material. The fabricated chip includes three electrolysis-based electrochemical pumps, one for loading the sample and the other two for delivering the solvent gradient; platinum electrodes for delivering current to the pumps and establishing the electrospray pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 26 publications
(42 reference statements)
0
109
0
Order By: Relevance
“…However, it is unclear whether sufficient separation power can be achieved with these fast liquid phase separations because the increase in the solvent gradient speed can degrade the separation peak capacity (60), which in turn reduces the overall dynamic range of detection. Other strategies for achieving robust fast separations include liquid phase chromatographic and electrophoretic separations on a microfluidic chip platform (62)(63)(64). Such chip-based separation devices also have the advantage of providing better robustness, reliability, and ease of operation.…”
Section: Analysis Throughputmentioning
confidence: 99%
“…However, it is unclear whether sufficient separation power can be achieved with these fast liquid phase separations because the increase in the solvent gradient speed can degrade the separation peak capacity (60), which in turn reduces the overall dynamic range of detection. Other strategies for achieving robust fast separations include liquid phase chromatographic and electrophoretic separations on a microfluidic chip platform (62)(63)(64). Such chip-based separation devices also have the advantage of providing better robustness, reliability, and ease of operation.…”
Section: Analysis Throughputmentioning
confidence: 99%
“…ESI is the method of choice for producing gas phase ions from solution because it is a very soft ionization method and is useful for the ionization of larger molecules or biomolecules. ESI-MS can be used for the analysis of complex mixtures [1][2][3][4][5] and is commonly used to couple separation techniques, such as high performance liquid chromatography (HPLC) [6][7][8][9], capillary electrophoresis (CE) [10][11][12][13][14][15][16][17][18][19][20][21], or microchannel electrophoresis (ME) [22][23][24][25][26][27][28][29] with MS. Many sample introduction methods, particularly those that employ separations, rely on pressure driven flow for sample introduction.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, they miniature the size and have the properties of fast response, less sample and low cost (Auroux et al, 2002) and this kind of sensing chip is also called Lab-on-a-chip. For example, the biosensors based on the field effect transistor (FET) made by MEMS immobilize anti-PSA on the carbon nanotubes (CNTs) (Kojima et al, 2005), liquid-chromatography-based biochip detects peptide mixture (Xie et al, 2005), and the biochip combines PCR-based DNA amplification and electrochemical detection (Lee et al, 2003) have been reported. Other few examples include antibody-based chips for determining protein isoform (Loonberg & Carlsson, 2006), liquid-chromatography-based chips for detecting peptide mixture (Xie et al, 2005), and electrophoresis-based chips for sensing catechol and dopamine (Schoning et al, 2005).…”
Section: Reviews and Motivationsmentioning
confidence: 99%
“…For example, the biosensors based on the field effect transistor (FET) made by MEMS immobilize anti-PSA on the carbon nanotubes (CNTs) (Kojima et al, 2005), liquid-chromatography-based biochip detects peptide mixture (Xie et al, 2005), and the biochip combines PCR-based DNA amplification and electrochemical detection (Lee et al, 2003) have been reported. Other few examples include antibody-based chips for determining protein isoform (Loonberg & Carlsson, 2006), liquid-chromatography-based chips for detecting peptide mixture (Xie et al, 2005), and electrophoresis-based chips for sensing catechol and dopamine (Schoning et al, 2005). Moreover, there are many choices for the materials of the microchannel, such as poly(dimethylsiloxane) (PDMS) (McDonald et al, 2000), poly(methyl-methacrylate) (PMMA) (Ford et al, 1998) and polycarbonate (PC) (Liu et al, 2001) … etc.…”
Section: Reviews and Motivationsmentioning
confidence: 99%